2015
DOI: 10.7554/elife.07320
|View full text |Cite
|
Sign up to set email alerts
|

A composite double-/single-stranded RNA-binding region in protein Prp3 supports tri-snRNP stability and splicing

Abstract: Prp3 is an essential U4/U6 di-snRNP-associated protein whose functions and molecular mechanisms in pre-mRNA splicing are presently poorly understood. We show by structural and biochemical analyses that Prp3 contains a bipartite U4/U6 di-snRNA-binding region comprising an expanded ferredoxin-like fold, which recognizes a 3′-overhang of U6 snRNA, and a preceding peptide, which binds U4/U6 stem II. Phylogenetic analyses revealed that the single-stranded RNA-binding domain is exclusively found in Prp3 orthologs, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 75 publications
(99 reference statements)
2
35
0
Order By: Relevance
“…This is consistent with a recent crystal structure of Prp3 in association with portions of U4/U6. 20 We compared the CmSnu13-RNA interaction 5 with reported observations for Snu13 orthologs. The dissociation constant, K D , for for CmSnu13 binding U4 snRNA was measured using fluorescence polarization with a 5'-fluorescein labeled RNA corresponding to U4 stem II, 5 nucleotides 22-50 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with a recent crystal structure of Prp3 in association with portions of U4/U6. 20 We compared the CmSnu13-RNA interaction 5 with reported observations for Snu13 orthologs. The dissociation constant, K D , for for CmSnu13 binding U4 snRNA was measured using fluorescence polarization with a 5'-fluorescein labeled RNA corresponding to U4 stem II, 5 nucleotides 22-50 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…11,[13][14][15][16][17][18] It has also been shown that Prp3p (human 90K) and Prp4p (human 60K) associate and require Snu13p to bind to U4 snRNA prior to their own assembly into the U4 snRNP. 14,20 It is not known what proteins are associated with U4 snRNA prior to assembly of the U4/U6 di-snRNP, but they may include the core Sm and Snu13 proteins. 14,21 In the second stage of U4/U6 snRNP assembly, Prp31 and Prp3/4 join independently.…”
Section: Introductionmentioning
confidence: 99%
“…of the U4/U6 duplex, formed by stem I, stem II, and an intervening U4 5′ stem loop (5′SL) (22,(29)(30)(31) (Fig. 1A).…”
mentioning
confidence: 99%
“…They bind U4/U6 di-snRNA in a hierarchical manner, with Snu13 required for Prp31 binding (29,32); both proteins together enhance binding of Prp3 (30,32). Snu13 and Prp31 bind the U4 5′SL and maintain additional contacts to stems I and II, whereas Prp3 binds stem II and a U6 3′-overhang (22,(29)(30)(31)(32)(33). However, it is presently not known how U4/U6-bound proteins influence Brr2-mediated U4/U6 unwinding, which regions of the U4/U6 di-snRNA Brr2 actively unwind, and how U4/U6 components segregate upon Brr2-mediated U4/U6 di-snRNP disruption.…”
mentioning
confidence: 99%
“…On the other hand, isolated Brr2 is a comparatively weak helicase, 25,40,41 and its U4/U6 di-snRNA substrate is stabilized by extensive base pairing and bound proteins, [12][13][14]29,42,43 suggesting that the helicase may also depend on specific activation to efficiently unwind the U4/U6 duplex at the right time.…”
Section: Brr2 Requires Tight Regulationmentioning
confidence: 99%